The pozzolanic activity of calcined oil-based drilling cuttings—aluminosilicate composites - Xiong, Deming; Wang, Chaoqiang (Environmental science and pollution research international, 2022)
In order to reduce the environmental impact of shale gas production and towards the attenuation of artificial pozzolanic materials production cost, new oil-based drilling cuttings (OBDCs) pozzolanic materials have been introduced. After calcination, the chemical composition and the pozzolanic activity of oil-based drilling cuttings residue (OBDCRs) were investigated. The combination of X-ray diffraction (XRD), thermogravimetric analysis (TG), and Fourier transform infrared (FTIR) techniques shed light on impacts of pretreatment, calcination temperature, and Ba 2+ on minerals’ structure and pozzolanic activity. The results showed that, after high temperature calcination, the components of Si or Al in the OBDCRs particle surface and structure were activated and recombined to produce corresponding activity. Ba 2+ could promote the pozzolanic activity of OBDCRs. The 28-day-compressive strength of OBDCRs was bigger than 31.33Mpa, and the compression strength ratios of cement mortar were bigger than 65%. Therefore, the pozzolanic reactivity of the treated OBDCs was competitive with that of conventional shale, which indicates that the heat treatment of OBDCs produces a cement substitute without any secondary pollution.